New Challenges in Surgical Approaches for Colorectal Cancer during the COVID-19 Pandemic - Dragos Serban; Geta Vancea; Catalin Gabriel Smarandache; Simona Andreea Balasescu; Gabriel Andrei Gangura; Daniel Ovidiu Costea; Mihail Silviu Tudosie; Corneliu Tudor; Dan Dumitrescu; Ana Maria Dascalu; Ciprian Tanasescu; Laura Carina Tribus (Applied Sciences, 2022)
(1) Background: The COVID-19 pandemic put a great burden on national healthcare systems, causing delays and disruptions in the medical care of non-COVID-19 patients. This paper aims to analyze the COVID-19 pandemic impact upon the quality of care in colorectal surgery. (2) Materials and Methods: We performed a retrospective study on the colorectal cancer cases operated in the Fourth Department of General Surgery, Emergency Hospital Bucharest Romania, over the period March 2020–February 2021 (pandemic group) vs. March 2019–February 2020 (non-pandemic group). (3) Results: The number of patients in the pandemic group decreased by 70% (36 vs. 118 patients), with lower accessibility from rural areas (11.1% vs. 37.2%, p = 0.035). Most cases in the pandemic group were emergencies (69% vs. 37.3%, p = 0.009), admitted for bowel obstruction (63.8% vs. 27.9%, p = 0.008). There was no in-hospital COVID-19 infection in patients operated for colorectal cancer. The 30-day mortality was significantly higher in the pandemic group (25% vs. 6.7%, p = 0.017), mostly due to septic shock (36.1% vs. 5%, p = 0.0001). (4) Conclusions: Colorectal cancer surgery may be performed safely during the COVID-19 pandemic, with strict adherence to the SARS-CoV-2 prevention protocols. However, the significant increase in colorectal cancers in the emergency was associated with worse outcomes and higher mortality during the COVID-19 pandemic.